Solve Radical Equation Like a Pro! | An Algebra Challenge

preview_player
Показать описание
Solve Radical Equation Like a Pro! | An Algebra Challenge

Welcome to family infyGyan!

In this algebraic video, we explore an exciting radical equation that’s sure to challenge our skills. This problem is an excellent exercise for anyone preparing for Math Olympiad or simply looking to deepen their understanding of advanced algebra. Follow along as we break down the steps to solve this complex equation, and try to solve it yourself before we reveal the solution. Perfect for students and math enthusiasts alike!.

If you enjoy tackling challenging math problems, be sure to like, share, and subscribe for more content like this!

📌 Topics Covered:

Radical equations
Problem-solving strategies
Factorization
Substitutions
Quadratic equations
Quadratic formula
Binomial Expansion
Synthetic division
Extraneous solutions
Rational root theorem
Real solutions
Verification

Additional Resources:

#math #radicalequation #algebra #problemsolving #education #matholympiad #matholympiadpreparation #tutorial #quadraticequations

🔔 Don't forget to subscribe and hit the bell icon to stay updated with our latest math challenges and tutorials. If you enjoy the video, please give it a thumbs up and share it with your friends!

💬 Comment below if you have any questions or if you were able to solve the problem. We love hearing from our viewers!

Thank you for watching videos and happy problem-solving!
Рекомендации по теме
Комментарии
Автор

Another approach.
p = ⁷√(27+x) and q = ⁷√(100-x) .
For the real p and q the identity holds
etc etc .

gregevgeni
Автор

Let a^7=27+x; b^7=100-x; => a+b=2-1; or -1+2; & a^7+b^7=128-1 or -1+128 = 2^7-1^7 or -1^7+2^7; =>27+x=128 or -1 => x =101 or -28; verified ✓

ShriH-do
Автор

Let _uₙ = aⁿ + bⁿ_
∴ _u₀ = 2, u₁ = 1, u₇ = 127_
Use: *_uₘ₊ₙ = uₘuₙ - uₘ₋ₙ(ab)ⁿ_*
_u₂ = u₁₊₁ = u₁² - u₀(ab)¹ = 1 - 2ab_
_u₄ = u₂₊₂ = u₂² - u₀(ab)² = (1 - 2ab)² - 2(ab)² = 1 - 4ab + 2(ab)²_
_u₃ = u₂₊₁ = u₂u₁ - u₁(ab)¹ = 1 - 2ab - ab = 1 - 3ab_
_127 = u₇ = u₄₊₃ = u₄u₃ - u₁(ab)³ = (1 - 4ab + 2(ab)²)(1 - 3ab) - (ab)³_
⇒ _7(ab)³ - 14(ab)² + 7ab + 126 = 0_
⇒ *_(ab)³ - 2(ab)² + ab + 18 = 0_*

guyhoghton
Автор

x = 101 or x = - 28
Put p = ⁷√(27+x) and q = ⁷√(100-x).
Then
p⁷+q⁷ = 127 (1) and p+q = 1 (2).
We have
p⁷+q⁷=(p³+q³)(p⁴+q⁴) - p³q³(p+q) (3)
Now
p³+q³=(p+q)³-3pq(p+q)= 1-3(pq) (4), due to (2).
Too p⁴+q⁴=(p²+q²)-2p²q² =
[(p+q)²-2pq]²-2p²q² = (1-2pq)²-2(pq)² = 1-4(pq)+2(pq)² (5), due to (2).
From (1), (2), (3), (4), (5) we have
p⁷+q⁷=(1-3(pq))•
•(1-4(pq)+2(pq)²)-(pq)³ =>
127 = -7(pq)³+14(pq)²-7(pq)+1 =>
m³ -2m²+m+18 =0 (6), m=pq.
(6) <=> (m+2)(m²-4m+9)=0 =>
m =-2 => pq =-2 (7).
From (2) and (7) => p, q roots of the equation t²-t-2=0 <=> (t-2)(t+1)=0 .
So (p, q)=(2, -1) or (p, q)=(-1, 2).
For p=2 => ⁷√(27+x)=2 => 27+x=2⁷=> x=101 .
For p=-1 => ⁷√(27+x)=-1 => 27+x=(-1)⁷ => x=-28.
So the solutions of the original equation are x=101 or x=-28 .

gregevgeni